Effects of cyanein and ramihyphin A on the dimorphism of Paracoccidioides brasiliensis - San-Blas, G; Yegres, F J (Folia microbiologica, 1978)
As a preliminary step in the study of dimorphism in Paracoccidioides brasiliensis, the effects of cyanein and ramihyphin A were studied. These antibiotics have been reported to induce morphological changes in fungi. The results obtained suggest that ramihyphin A induce swelling of hyphae while partially inhibiting Y leads to M transformation with the production of an incipient and swollen mycelium. Cyanein did not affect the mycelial morphology as did ramihyphin A. However, the Y leads to M transformation was inhibited and, also, the M leads to Y transformation was blocked with the production of a few yeast cells which were not released from the mycelium.
Keywords: houby; Transformation, Genetic; Polymorphism, Genetic; transformace genetická; Paracoccidioides; Cyclopentanes; cyklopentany; Antifungal Agents; Fungi; polymorfismus genetický; antifungální látky